2020
DOI: 10.3390/medicina56070342
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium in Patients with Chronic Obstructive Pulmonary Disease after Coronary Artery Bypass Grafting

Abstract: Background and Objectives: The incidence of postoperative delirium (POD) in patients with chronic obstructive pulmonary disease (COPD) is unclear. It seems that postoperative respiratory problems that may occur in COPD patients, including prolonged mechanical ventilation or respiratory-tract infections, may contribute to the development of delirium. The aim of the study was to identify a relationship between COPD and the occurrence of delirium after cardiac surgery and the impact of these combined diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Brunna et al found that COPD increased the risk of POD during hospitalization of elderly fracture patients (Lima et al, 2021 ). COPD had also been identified as a risk factor for POD in other diseases, such as coronary artery bypass grafting (CABG; Szylińska et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brunna et al found that COPD increased the risk of POD during hospitalization of elderly fracture patients (Lima et al, 2021 ). COPD had also been identified as a risk factor for POD in other diseases, such as coronary artery bypass grafting (CABG; Szylińska et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple causes of delirium in COPD patients, and there is currently no specific drug treatment available [14]. Clinical studies have confirmed that alle- viating the onset of delirium in patients is often beneficial for the treatment of COPD [5].…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients are mostly elderly patients. The cause of delirium is the abnormal function of neurotransmitter and the damage of blood–brain barrier [ 28 30 ]. The receptivity of the brain of the elderly to external stimuli decreases, and the inflammation response increases, which is manifested by the progressive apoptosis of the cells in the brain of the elderly, the decline of brain function, and the decrease of the activity of neurotransmitter synthase in the brain with aging [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%